2015
DOI: 10.1186/s40478-015-0192-4
|View full text |Cite
|
Sign up to set email alerts
|

IFNβ secreted by microglia mediates clearance of myelin debris in CNS autoimmunity

Abstract: Introduction: Multiple sclerosis (MS) is a chronic demyelinating disorder of the central nervous system (CNS) leading to progressive neurological disability. Interferon β (IFNβ) represents a standard treatment for relapsing-remitting MS and exogenous administration of IFNβ exhibits protective effects in experimentally induced CNS autoimmunity. Also, genetic deletion of IFNβ in mice leads to an aggravation of disease symptoms in the MS model of experimental autoimmune encephalomyelitis (EAE). However, neither t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 58 publications
(70 reference statements)
3
72
0
1
Order By: Relevance
“…Microglia is verified to play an important role in the process of remyelination (Voss et al, 2012; Miron et al, 2013; Doring et al, 2015; Lampron et al, 2015). Accumulating evidence suggests that microglia is associated with the clearance and phagocytosis of degraded and collapsed myelin debris, existence of which is detrimental to OPC proliferation and remyelination (Kotter et al, 2005, 2006; Ruckh et al, 2012; Kocur et al, 2015). Studies also found that microglia, especially M2 phenotype, are positively related to the recruitment of OPCs and their differentiation into mature oligodendrocytes, as well as myelin formation (Miron et al, 2013; Wang et al, 2015; Marteyn et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Microglia is verified to play an important role in the process of remyelination (Voss et al, 2012; Miron et al, 2013; Doring et al, 2015; Lampron et al, 2015). Accumulating evidence suggests that microglia is associated with the clearance and phagocytosis of degraded and collapsed myelin debris, existence of which is detrimental to OPC proliferation and remyelination (Kotter et al, 2005, 2006; Ruckh et al, 2012; Kocur et al, 2015). Studies also found that microglia, especially M2 phenotype, are positively related to the recruitment of OPCs and their differentiation into mature oligodendrocytes, as well as myelin formation (Miron et al, 2013; Wang et al, 2015; Marteyn et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The same deletion in B or T cells had no effect on disease severity (Prinz et al 2008). Further depicting the role of IFN-β in microglia, Kocur et al (2015) used IFN-β-florescent reporter mice to show that microglia are the major producers of IFN-β at the peak stage of EAE and accomplish IFN-β-induced clearance of myelin debris.…”
Section: Ifn-βmentioning
confidence: 99%
“…also found that IFN signaling in myeloid cells, but not in lymphocytes or neural cells, is required for protection against EAE. In agreement with this, Kocur et al . showed that microglia produce IFN‐β at the peak of EAE, and that IFN‐β enhances the capacity of microglia to clear myelin debris in an autocrine fashion.…”
Section: Endogenous Type I Ifn In Msmentioning
confidence: 57%